2019
DOI: 10.3390/molecules24213954
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin Assisted Liquid–Liquid Microextraction Based on Solidification of the Floating Organic Droplets Method for Determination of Neonicotinoid Residues

Abstract: An efficient and environment-friendly microextraction method, namely, β-cyclodextrin assisted liquid–liquid microextraction, based on solidification of the floating organic droplets method coupled with HPLC is investigated for the sensitive determination of trace neonicotinoid pesticide residues. In this method, β-cyclodextrin is used as a disperser solvent, while 1-octanol is selected as an extraction solvent. β-cyclodextrins was found to decrease interfacial tension and increase the contact area between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Vichapong et al reported a microextraction method for the detection of the neonicotinoid pesticides thiamethoxam, clothianidin, imidacloprid, acetamiprid and thiacloprid. [126] The system was based on β-cyclodextrin assisted liquid-liquid microextraction, which involved a solidification process (of floating droplets) in combination with HPLC. The presence of the βcyclodextrin (disperser solvent) aided, along with centrifugation, the process by increasing the organic and aqueous phase contact area, whilst at the same time reducing the interfacial tension.…”
Section: Use Of Liquid-liquid Microextractionmentioning
confidence: 99%
“…Vichapong et al reported a microextraction method for the detection of the neonicotinoid pesticides thiamethoxam, clothianidin, imidacloprid, acetamiprid and thiacloprid. [126] The system was based on β-cyclodextrin assisted liquid-liquid microextraction, which involved a solidification process (of floating droplets) in combination with HPLC. The presence of the βcyclodextrin (disperser solvent) aided, along with centrifugation, the process by increasing the organic and aqueous phase contact area, whilst at the same time reducing the interfacial tension.…”
Section: Use Of Liquid-liquid Microextractionmentioning
confidence: 99%
“…To date, numerous sample preparation methods for analysis have been developed. These include liquid–liquid extraction (Timofeeva et al 2017 ), liquid phase microextraction (Vichapong et al 2013 , 2019 ; Kachangoon et al 2020a , 2020b ), solid-phase extraction (Wang et al 2020b ; Zaidon et al 2019 ; Ghiasi et al 2020 ), QuEChERS (Paradis et al 2014 ; Tanner and Czerwenka 2011 ), and anion exchange-disposable pipette extraction (Song et al 2018 ). Following sample preparation, the next essential step is selecting the appropriate analytical method.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In DLLME, a combination of extractant and dispersive solvent is swily injected into the aqueous sample phase to generate a cloudy solution. 11 This results in faster extraction times, 12 due to its simplicity, 13 yields high enrichment factors and can easily be combined with other analytical method. DLLME thus has certain advantages over the classic methods of pretreatment.…”
Section: Introductionmentioning
confidence: 99%